2013
DOI: 10.1108/oclc-12-2012-0042
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and use of Web 2.0 tools by librarians in university libraries in Nigeria

Abstract: PurposeThe study aims to investigate the level of awareness and use of Web 2.0 tools by librarians in university libraries in Nigeria.Design/methodology/approachA questionnaire was used to collect data from 176 librarians in 49 university libraries in Nigeria.FindingsIt emerged that the librarians were more familiar with social networking sites, instant messaging, media sharing sites, blogs and wikis. The popularity of these Web 2.0 tools made them the most frequently used by the librarians. Web 2.0 tools like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 29 publications
5
17
0
2
Order By: Relevance
“…Consistent with recent studies advocating the awareness and use of Web 2.0 tools by students in different fields e.g. [23], [24]. The findings indicated that majority of the first year IS students in WU were aware of Web 2.0 tools and they made moderate use of YouTube, Blogs, Wikis, Social Bookmarks, Instant messaging, and Facebook.…”
Section: Discussionsupporting
confidence: 77%
“…Consistent with recent studies advocating the awareness and use of Web 2.0 tools by students in different fields e.g. [23], [24]. The findings indicated that majority of the first year IS students in WU were aware of Web 2.0 tools and they made moderate use of YouTube, Blogs, Wikis, Social Bookmarks, Instant messaging, and Facebook.…”
Section: Discussionsupporting
confidence: 77%
“…Apesar de existir uma inversão quanto ao lugar ocupado pelo blog e facebook nas bibliotecas das IES Estaduais (facebook -12,1% -blog -27,6%) e das IFES (blog-17,8% -facebook -22,2%), observa-se que depois do twitter, esses dispositivos são os que mais se destacam quanto à utilização pelas bibliotecas centrais e/ou sistemas de bibliotecas das universidades públicas brasileiras, resultado que se aproxima do identificado por Baro, Idiodi e Godfrey (2013), no contexto das bibliotecas universitárias na Nigéria.…”
Section: Apresentação E Discussão Dos Resultadosunclassified
“…A scholar-made questionnaire was used to gather the data (Appendix 1). The questionnaire was designed through reviewing related literature (Baro et al, 2012;Garoufallou and Charitopoulou, 2011) and research questions. It was used to collect data on the awareness and use of Web 2.0 tools among librarians.…”
Section: Research Objectives and Methodologymentioning
confidence: 99%
“…These barriers may be associated with such factors as limited infrastructure and other information-based technologies, lack of library-centered social media policies and lack of funding for training and resources (Collins and Quan-Haase, 2013). Also, reduced availability of facilities, such as computers with internet access, lack of time and lack of skills, was considered as a barrier in the use of Web 2.0 tools by librarians in Nigeria (Baro et al, 2012). Isfandyari-Moghaddam and Hosseini-Shoar (2014) identified factors affecting the adoption of Web 2.0 tools by librarians of academic libraries in Hamedan, EL 34,6 Iran.…”
Section: Literature Reviewmentioning
confidence: 99%